Program Petugas Kedisiplinan Kelas Inovasi Penanaman Karakter Disiplin di Sekolah Dasar - Rifka Anisa; Mohammad Adam Jerusalem (IKIP PGRI Bojonegoro, 2019)
Abstract: This article aims to explore the innovation program of class discipline officers to instill the value of discipline character in elementary school students. This article describes in a straightforward and in-depth manner about a program innovation created by the teacher with a student center approach and in accordance with the characteristics of elementary school students. The research design used in this article is qualitative research with a type of case study research involving 6 students, 1 teacher, and 1 principal for in-depth and comprehensive interviews. The results showed that there were three steps in carrying out the disciplinary officer program namely planning, implementing and evaluating. Class discipline officers are innovations in character education programs where students act as officers to maintain discipline and class discipline. This program-centered approach makes students gain real experience so that it is easy for students to understand. Therefore, this class discipline disciplinary program is suitable for application in elementary schools. Contributions in this study are expected to be able to: 1) Provide input in increasing attention in instilling the values of student discipline. 2) Increase awareness for schools to integrate discipline values in formulating school activities policies and programs.Â Abstrak: Artikel ini bertujuan mengeksplorasi inovasi program petugas kedisiplinan kelas untuk menanamkan nilai karakter disiplin pada siswa sekolah dasar. Artikel ini mendeskripsikan secara lugas dan mendalam mengenai suatu inovasi program yang diciptakan guru dengan pendekatan student center dan sesuai dengan karakteristik siswa sekolah dasar. Desain penelitian yang digunakan dalam artikel ini yakni penelitian kualitatif dengan jenis penelitian studi kasus yang melibatkan 6 siswa, 1 guru, dan 1 kepala sekolah untuk wawancara secara mendalam dan komprehensif. Hasil penelitian menunjukkan bahwa terdapat tiga langkah dalam melaksanakan program petugas kedisiplinan kelas yakni perencanaan, pelaksanaan, dan evaluasi. Petugas kedisiplinan kelas merupakan inovasi program pendidikan karakter dimana siswa yang berperan sebagai petugas guna menjaga kedisiplinan dan ketertibab kelas. Pendekatan yang berpusat pada program ini membuat siswa mendapatkan pengalaman secara nyata sehingga mudah dipahami siswa. Oleh karena itu, program petugas kedisiplinan kelas ini cocok untuk diterapkan di sekolah dasar. Kontribusi dalam penelitian ini yakni diharapkan mampu: 1) Memberikan masukan dalam meningkatkan perhatian dalam menanamkan nilai kedisiplinan siswa. 2)Meningkatkan kesadaran bagi sekolah untuk mengintegrasikan nilai kedisiplinan dalam merumuskan kebijakan dan program kegiatan sekolah.Â Â